DOZ047.121: Usefulness of conservative treatment in recurrent tracheoesophageal fistula in children. (24th June 2019) - Isoldi, S; Torroni, F; Faraci, S; Balassone, V; Rea, F; Tambucci, R; Angelino, G; Romeo, E F; Guerra, L; Caldaro, T; Contini, A C I; di Abriola, G F; et al.
Abstract: Introduction: Recurrent tracheoesophageal fistula (TEF) is a challenging complication in children with repaired esophageal atresia (EA). Thoracotomy, with surgical repair, is the traditional therapeutic approach, however it is often associated with a significant morbidity and technical difficulty. Endoscopic techniques, from the tracheal and/or esophageal side, have recently been proposed as a primary treatment, in order to prevent reoperation especially in previously operated fields. Aim of this retrospective study is to present our experience as Tertiary Care Center and Referral Center for EA, on the endoscopic management of recurrent TEF in children with repaired EA. Method: This is a retrospective study conducted on children with repaired EA referred at Bambino Gesù Children's Hospital from January 2009 to January 2019. Demographic and clinical details, including type of EA, presence of fistula, concomitant malformations, endoscopic evaluation, number and kind of treatments, performed were collected. Results: We identified 171 patients with EA, 15 type 1 (9%), 7 type 2 (4%), 140 type 3 (82%), 6 type 4 (3%), 3 type 5 (2%). Among patients with TEF, 11/156 (7%- M:F/6:5) presented with a TEF recurrence. Among the latter, 5 (45.4%) were patients with concomitant malformation (2 VACTER, 2 anorectal malformation, 1 Down syndrome, cardiac abnormalities, and hypothyroidism). All patients with TEF recurrence presented with symptoms, such as chronic cough, vomit, bronchitis, recurrent pneumonia, and failure to thrive. All patients underwent endoscopic evaluation both from digestive and tracheal side. Six (6/11–54.5%) patients underwent surgery, 5 patients (5/11–45.4%) were treated with endoscopic transtracheal fibrin glue injection after brushing that was successful in two patients (2/5–40%), one patient needed a retreatment. These patients maintained successful closure after treatment confirmed at endoscopic follow-up. Remaining three patients needed surgical approach during follow-up. Conclusion: Endoscopic repair of recurrent TEF has proved safe and effective in the literature as an alternative to a second open thoracotomy/surgical repair. In our series, although in two cases, it represented a valid alternative to surgery. We suggest that it is worthy to try a conservative approach before surgery.